Potensi Pembentukan Trihalometana (THM) Selama Proses Klorinasi pada Air Sungai Maruni dan Air Kali SP 6 di Kabupaten Manokwari - Markus Heryanto Langsa; Pramesty Wulan Ramadhanty; Maria Ludya Pulung (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
The purpose of this study was to determine the potential formation of THM in surface water sources, namely Maruni River water and SP 6 River water in Manokwari Regency. Each sample was characterized for its physical and chemical characteristics including parameters of Total Organic Carbon (TOC), total suspended solids (TSS), ammonia, pH, turbidity, and conductivity (DHL). The ideal/correct concentration for chlorination of water samples is determined based on the need for chlorine which leaves a residual chlorine of 0.5 mg Cl2/L for 24 hours. The TOC content of the Maruni River and SP 6 River water samples were 0.5 mg C/L and 17.2 mg C/L, respectively. Both water samples were chlorinated with chlorine concentrations of 3.44 mg Cl2/L and 10.36 mg Cl2/L, respectively. In Maruni River water, the concentration of THM (read as chloroform) formed was 6.5 µg/L and Kali SP 6 water was 577.5 µg/L. The level of chloroform formed in the Maruni River water sample is very low compared to the required quality standard according to Health of Indonesian Ministry No. 907 of 2002 regarding requirements and monitoring of drinking water quality, which is 200 µg/L, so that the Maruni River water can be treated by chlorine to be used as drinking water.